2021
DOI: 10.1007/s12665-021-09507-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of groundwater salinity using geophysical and geochemical approaches: heuningnes catchment coastal aquifer. Western Cape Province, South Africa

Abstract: Seawater intrusion is recognised as a major factor affecting the quality of groundwater in coastal aquifers around the world. To determine the occurrence and extent of saline groundwater intrusion prevailing in the Heuningnes Catchment, a 2D resistivity imaging survey was carried out in three sites within the catchment. Eleven resistivity profile lines were conducted using the multi-electrode ABEM SAS resistivity meter system, employing the Wenner Array to map the extent of saline groundwater. A 2D resistivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
3
1
0
2
Order By: Relevance
“…A recent study on coastal groundwater in Bhola District, Bangladesh, reported an average EC of 588.15 µS/cm [46], indicating a notable difference between the two reports. However, the EC values observed in this study align with those found in coastal aquifers of Southern Kenya [47], Western Cape Province, South Africa [48], and South [49]. Typically, fresh groundwater unaffected by saltwater intrusion exhibits mild salinity and, thus, low EC values.…”
Section: Physical Parameterssupporting
confidence: 83%
“…A recent study on coastal groundwater in Bhola District, Bangladesh, reported an average EC of 588.15 µS/cm [46], indicating a notable difference between the two reports. However, the EC values observed in this study align with those found in coastal aquifers of Southern Kenya [47], Western Cape Province, South Africa [48], and South [49]. Typically, fresh groundwater unaffected by saltwater intrusion exhibits mild salinity and, thus, low EC values.…”
Section: Physical Parameterssupporting
confidence: 83%
“…This finding is similar to those in Tshikondeni, which is part of the Soutpansberg Basin, that indicated that the Na + + Cl − /(Na + + K + + Ca 2+ ) ratio was greater than >0.5 (ion exchange) and the weathering of rocks influenced the groundwater chemistry [21]. In this study, the classification used in [47] was adopted, where parameters with a correlation coefficient >0.7 were considered to be strongly correlated. Parameters with correlation coefficient >0.5 to <0.7 were considered to have a moderate correlation and a correlation coefficient less than 0.5 indicated that there was no relationship between the parameters.…”
Section: Hydro-geochemical Processessupporting
confidence: 76%
“…A strong correlation (r = 1) between Na + and Cl − indicates that these parameters originated from the same source. The correlation coefficient between TDS and In this study, the classification used in [47] was adopted, where parameters with a correlation coefficient >0.7 were considered to be strongly correlated. Parameters with correlation coefficient >0.5 to <0.7 were considered to have a moderate correlation and a correlation coefficient less than 0.5 indicated that there was no relationship between the parameters.…”
Section: Hydro-geochemical Processesmentioning
confidence: 99%
“…Em adição, Carvalho & Souza (2022) discutem a influência do clima em águas superficiais e subterrâneas no município de Carnaúba dos Dantas/RN, evidenciando o papel que a irregularidade das chuvas tende a exercer na distribuição iônica tanto em águas superficiais quanto subterrâneas. Comumente, as águas associadas a reservatórios em unidades aquíferas fissurais submetidas a um regime de chuvas irregular, se encontram salinizadas, impactando seu eventual uso na irrigação (Nogueira et al, 2019;Mokoena et al, 2021). Geralmente, essas águas apresentam quantitativos de sólidos totais dissolvidos elevados e que as tornam inadequadas ao consumo humano e uso agrícola, ou no limiar entre a possibilidade de seu uso ou descarte (Batarseh, 2017;Qaisar et al, 2018;Batarseh et al, 2021).…”
Section: Introductionunclassified